1-D finite strain consolidation analysis based on isotach plasticity: Class A and Class C predictions of the Ballina embankment. (January 2018) - Yang, Chao; Carter, John P.
Abstract: Trial embankments with prefabricated vertical drains (PVDs) or Jute drains were constructed on the National Soft Soil Field Testing Facility (NFTF) at Ballina, NSW, Australia. The results of extensive laboratory and in situ testing and sophisticated field instrumentation of the soils at the site offer an excellent opportunity to investigate the mechanical behaviour of natural estuarine soft clays. An advanced hierarchical constitutive model based on isotach plasticity, viz., the Hunter Clay (HC) model, was used to characterise key features of this soft clay, including the effects of inter-particle cementation, fabric anisotropy and strain rate dependency of the soil behaviour. Incorporation of the HC model into finite strain consolidation theory leads to a fully coupled hydro-mechanical analysis of natural soft clays. The finite difference method, incorporating an explicit solution scheme, was used to solve numerically the highly non-linear partial differential equation governing this initial value problem. A Class A prediction of the settlement of a PVD-treated embankment was carried out. Comparison of this Class A prediction with field measurements of settlement and excess pore water pressure indicated the need for more accurate characterisation of the effects of PVD installation, particularly in terms of the value of the equivalent permeability that was adopted in a simple one-dimensional consolidation analysis of the embankment problem. A Class C numerical prediction was subsequently conducted, showing the capacity to capture accurately the evolution of settlements with time as well as the dissipation of excess pore pressures at various depths in the clay profile. It was found that the Hunter Clay model was able to successfully characterise the mechanical behaviour of the natural soft clay at Ballina, demonstrating its potential for implementation in numerical methods to solve boundary and initial value problems in geotechnical engineering.